Macrodactyly Lipomatosa in the Left Index Finger and Thumb: A Radiological and Clinical Perspective - Shreyosi Santra; Vivek Khanna; Shishir Chumber; Kavita Vani (Journal of Clinical and Diagnostic Research, 2024)
Macrodystrophia Lipomatosis (MDL) is a rare congenital, non-hereditary, and benign form of gigantism characterised by the overgrowth of adipose tissue in a specific area of the body, usually affecting the hand or foot in the distribution of the median and plantar nerves, respectively. Here, the authors present a case of a 21-year-old male patient, who presented to the Surgical Outpatient Department (OPD) with the gradual, progressive enlargement of the left index finger and thumb over the last six months, experiencing difficulty in holding objects and maintaining grip. This case highlights the importance of radiological imaging in diagnosis and treatment planning. Macrodystrophia lipomatosis should be considered as a differential diagnosis for hypertrophic digits, even in adult patients.